Reactions of PhIX2 I(iii) oxidants with heavy triphenyl pnictines. Issue 22 (26th May 2020) - Egalahewa, Sathsara; Aprile, Antonino; Dutton, Jason L.
Abstract : Oxidation of heavy triphenyl pnictines with Weiss' reagent ([PhI(Pyr)2 ] 2+ ) gives dicationic Pn(v ) coordination complexes in a single step. Abstract : The reactions of [PhI(pyridine)2 ] 2+, PhI(OAc)2 and PhI(OTf)(OAc) with Ph3 As, Ph3 Sb and Ph3 Bi are described. The reactions of [PhI(pyridine)2 ] 2+ with Ph3 Sb and Ph3 Bi afford dicationic Pn(v ) complexes ligated by pyridine in one step. These were previously reported by Burford in multi-step syntheses. Reactions with PhI(OAc)2, which were already known for Sb and Bi giving Pn(v ) diacetates, were confirmed to give the same type of compound for As. Reactions with PhI(OAc)(OTf) were less selective, resulting in the isolation of iodonium cations [Ph–I–Ph] + for As and Bi, while Ph3 Sb gave an oxobridged di-antimony species characteristic of the decomposition of a high valent triflate bound species.